Bringing Brands to Life: The Mediating Role of Brand Attachment in the Relationship between Brand Anthropomorphism, Brand Love, and eWOM - Arif , Hajra; Muhammad, Ghulam; Ahmed, Rizwan Raheem (Transformations In Business & Economics, 2026)
Brand anthropomorphism, defined as the act of personifying brands, has gained significant attention from research scholars within the current market. The present research investigates how brand anthropomorphism, a powerful branding strategy, promotes brand attachment, particularly in the confectionery industry. The study employs the theory of attachment and anthropomorphism. Responses from 463 participants were collected via social media, specifically from those who interacted with anthropomorphised brands used in the confectionery industry. PLS-SEM was employed to analyse the relations between variables and examine the mediating role of attachment with the brands. Results confirmed that anthropomorphic brands significantly enhance attachment and help strengthen brand love, thus inspiring consumers towards a positive electronic word-of-mouth (eWOM). The analysis reveals that brand attachment fully mediates the effect of anthropomorphism on brand love and partially mediates its impact on eWOM. The results propose that brand humanisation can be a powerful approach to building emotional connections, driving consumer encouragement, and strengthening brand perceptibility through eWOM. The research provides valuable insights for marketers, highlighting the importance of anthropomorphism in fostering stronger consumer relationships with the brand, leveraging these bonds to establish long-term relationships and promote a positive eWOM.
Keywords: brand anthropomorphism; brand love; brand attachment; e-word of mouth; confectionery industry; anthropomorphism theory; attachment theory